CSP41, a sequence-specific chloroplast mRNA binding protein, is an endoribonuclease. - Yang, J (1996)
Correct 3' processing of chloroplast precursor mRNAs (pre-mRNAs) requires a stem-loop structure within the 3' untranslated region. In spinach, a stable 3' stem-loop-protein complex has been shown to form in vitro between petD pre-mRNA, encoding subunit IV of the cytochrome b6/f complex, and chloroplast proteins. This complex contains three chloroplast stem-loop binding proteins (CSPs), namely, CSP29, CSP41, and CSP55. Here, we report the purification of CSP41 and cloning of the csp41 gene and show that CSP41 is encoded by a single nuclear gene. Characterization of bacterially expressed CSP41 demonstrates that this protein binds specifically to the 3' stem-loop structure and a downstream AU-rich element of petD pre-mRNA and that its binding affinity is enhanced by associating with CSP55. Our data also show that CSP41 has substantial nonspecific endoribonuclease activity. These data suggest that CSP41 could be involved in 3' processing of petD pre-mRNA and/or in RNA degradation. The fact that different reaction conditions favor RNA binding over ribonuclease activities suggests a possible mode of in vivo regulation.